The GATAD2B-NuRD complex drives DNA:RNA hybrid-dependent chromatin boundary formation upon DNA damage - Liu, Z; Ajit, K; Wu, Y; Zhu, W; Gullerova, M (EMBO Press, 2024)
Double-strand breaks (DSBs) are the most lethal form of DNA damage. Transcriptional activity at DSBs, as well as transcriptional repression around DSBs, are both required for efficient DNA repair. The chromatin landscape defines and coordinates these two opposing events. However, how the open and condensed chromatin architecture is regulated remains unclear. Here, we show that the GATAD2B–NuRD complex associates with DSBs in a transcription- and DNA:RNA hybrid-dependent manner, to promote histone deacetylation and chromatin condensation. This activity establishes a spatio-temporal boundary between open and closed chromatin, which is necessary for the correct termination of DNA end resection. The lack of the GATAD2B–NuRD complex leads to chromatin hyperrelaxation and extended DNA end resection, resulting in homologous recombination (HR) repair failure. Our results suggest that the GATAD2B–NuRD complex is a key coordinator of the dynamic interplay between transcription and the chromatin landscape, underscoring its biological significance in the RNA-dependent DNA damage response.